(2a-3b)(2a+3b)(4a平方-9b平方)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 00:48:28
(2a-3b)(2a+3b)(4a平方-9b平方)(2a-3b)(2a+3b)(4a平方-9b平方)(2a-3b)(2a+3b)(4a平方-9b平方)(2a-3b)(2a+3b)(4a²-9
(2a-3b)(2a+3b)(4a平方-9b平方)
(2a-3b)(2a+3b)(4a平方-9b平方)
(2a-3b)(2a+3b)(4a平方-9b平方)
(2a-3b)(2a+3b)(4a²-9b²)
=(4a²-9b²)(4a²-9b²)
=(4a²-9b²)²
=(4a²)²-2(4a²)(9b²)+(9b)²
=16a的4次方-72a²b²+81b的4次方
请点击下面的【选为满意回答】按钮.
(2a-3b)(2a+3b)(4a²-9b²)
=[(2a)²-(3b)²](4a²-9b²)
=(4a²-9b²)(4a²-9b²)
=(4a²-9b²)²
=(4a²)²-2×(4a²)×(9b²)+(9b²)²
=16a^4-72a²b²+81b^4
a平方b-[a平方b-(2abc-a平方c-3a平方b)-4a平方c]-abc
计算(1)(ab-b平方)/a平方-b平方/a+b(2)a-ab/a+b*(a+b)平方 /b平方-1 (3)a-1/a平方-4a+4/a平方-1/a平方-4
(a-3)平方-(2a-b)平方
合并同类项3(a-b)的平方+(a+b)-2(a+b)-(a-b)的平方-4(a+b).
(a-2b)(a-3b)+(a-2b)平方-(a-3b)平方
-3(2a-b)平方+4(2a-b)2-8(2a-b)平方
(2a-3b)(2a+3b)(4a平方-9b平方)
(2a+4b)(3a-6b)(a平方+4b平方)=
(a+2b)(3a-6b)(a的平方+4b的平方) 急
(a+3b)平方-2(a+3b)(b-3b)+(a-3b)的平方
分式(a+b/a-b)平方*2a-2a/3a+3b-a平方/a平方-b平方除于a/b要怎么算?
(3a+2b)平方-(2a+3b)平方
(a+3b)(a-3b)-(3a-b)的平方+(4a+5b)·(a+2b)
(3a+2b)平方-(2b+a)平方
化简(4a平方-3b平方)-【2(2a平方-1)+2b平方-3】
因式分解:9(a-b)平方-(2a-3b)平方
(a+2b)平方-(a-3b)平方
a的平方b-(-3ab平方)+(-4a平方b)-2ab平方=